Real world outcomes of Kahook Dual Blade goniotomy in black and Afro-Latinx adult patients with glaucoma: a 2-year retrospective study - Adebayo, Ayobami; Ng, Chester; Laroche, Daniel (Frontiers in Ophthalmology, 2025)
BackgroundThe Kahook Dual Blade goniotomy has been shown to be efficacious in the treatment of open angle glaucoma. We previously reported 6 months results using the Kahook Dual Blade in Black and Afro-Latino patients.ObjectivesThe purpose of this study was to determine the effectiveness and safety of Kahook Dual Blade (KDB) goniotomy alone or coupled with phacoemulsification cataract surgery to minimize intraocular pressure, number of medications used and visual field preservation in Black patients or Afro-Latinx who have open-angle glaucoma (OAG).DesignThis was a retrospective, nonrandomized study that was carried out at two private practices in Harlem, NY and Queens, NY.MethodsThis study consisted of patients with OAG who underwent phacoemulsification combined with goniotomy (PE + KDB) or goniotomy alone (KDB). The Kahook dual blade was used to perform goniotomy in all patients. Reduction of intraocular pressure (IOP) and alleviating the burden of medications were both considered indications for glaucoma surgery. Our research included information on IOP before and after surgery, the number of medications to decrease IOP pressure, visual field mean deviation, during a follow-up period of two years.ResultsAt two years we identified 31 patients who had surgery. The preoperative IOP of all 31 eyes which had surgery was 16.7 mmHg which decreased to 14.0 mmHg after two years. The baseline number of topical IOP-lowering medications was 2.4 ± 1.4 at baseline which decreased to 1.6 ± 1.4 (P = 0.02) after two years. The average visual field mean deviation was stable in both groups after two years. Postoperative adverse events were mild and included transient hyphema, IOP spikes, posterior capsule opacification, tearing, glare and mild pain.ConclusionIn Black or Afro-Latinx patients with open-angle glaucoma, phacoemulsification coupled with Kahook dual-blade goniotomy considerably reduces IOP and the number of medications.